A simple model to estimate hydrogen solubility in liquid aluminium alloys. (3rd May 2020) - Tiryakioğlu, Murat
ABSTRACT: Data for solubility of hydrogen in binary liquid aluminium alloys have been reanalysed by normalising alloy hydrogen solubility data with that for pure aluminium reported in the same study. This method has eliminated one source of variation, namely due to difference in experimental conditions between studies. Analysis has shown the effect of Cu, Mg, Si and Zn additions on normalised hydrogen solubility can be estimated by using exponential fits. The method is also demonstrated to provide accurate estimates for three multicomponent alloys.